Evaluation of Traumatic Corneal Rupture Treatment Outcome in dr. Cipto Mangunkusumo Hospital: Two Years Retrospective Study - Brenda Hayatulhaya; Syska Widyawati (Faculty of Medicine Universitas Indonesia, 2021)
Open globe injury is an injury that requires prompt treatment which could predict the final outcome. This study evaluates the characteristics and outcome of corneal rupture management in dr. Cipto Mangunkusumo National Hospital’s emergency room. We conducted a retrospective study based on the patient’s medical record between January 2016 – December 2017. Data regarding patients’ demographic, clinical characteristics according to Birmingham Eye Trauma Terminology Score (BETTS) criteria, duration of trauma to surgery, use of early topical steroid, one month visual function result, and risk of endophthalmitis were collected. A repeated ANOVA test with posthoc Bonferroni was used to compare the mean of a paired numeric variable. A total of 163 patients with corneal rupture were recorded, consisted of mostly male (92%) and median age of 27 years old. We found 36.8% cases occurred in the household, 71% cases in the zone I, 62.6% penetrating cases, and mostly came with 4/200-light perception visual acuity (VA) for all zones, mostly caused by inorganic materials and 50.9% cases involved lens. Endophthalmitis was higher in inorganic causes (69.2% vs 30.8%, p=0.33). A total of 95.2% of cases performed surgical treatment in < 24 hours. In post-operative follow up, 53.3% of cases did not need re-operation or proceeding surgery. Several risk factors might affect the treatment outcome of eye injury. Most rupture occurred at zone I. Administration of topical steroids directly post-surgery was not associated with the incidence of endophthalmitis.